2008
DOI: 10.1679/aohc.71.249
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule remodeling mediates the inhibition of store-operated calcium entry (SOCE) during mitosis in COS-7 cells

Abstract: the natural mitotic microtubule remodeling that was also accompanied by SOCE inhibition. Short exposure to paclitaxel, a microtubule-stabilizing drug, bolstered SOCE, whereas long exposure resulted in microtubule disruption and SOCE inhibition. Actin-modifying drugs did not affect SOCE. These findings indicate that mitotic microtubule remodeling plays a significant role in the inhibition of SOCE during mitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…More recent studies confirmed that SOCE is inactivated during mitosis in HeLa, RBL-2H3, HEK293 and Cos-7 cells (Russa et al, 2008;Smyth et al, 2009;Tani et al, 2007). Investigating SOCE levels throughout the cell cycle showed that there is a slight enhancement of SOCE during the G1 and S phases, and dramatic downregulation during M phase (Tani et al, 2007).…”
Section: Soce Inactivates During Mitosismentioning
confidence: 87%
See 3 more Smart Citations
“…More recent studies confirmed that SOCE is inactivated during mitosis in HeLa, RBL-2H3, HEK293 and Cos-7 cells (Russa et al, 2008;Smyth et al, 2009;Tani et al, 2007). Investigating SOCE levels throughout the cell cycle showed that there is a slight enhancement of SOCE during the G1 and S phases, and dramatic downregulation during M phase (Tani et al, 2007).…”
Section: Soce Inactivates During Mitosismentioning
confidence: 87%
“…Investigating SOCE levels throughout the cell cycle showed that there is a slight enhancement of SOCE during the G1 and S phases, and dramatic downregulation during M phase (Tani et al, 2007). It has also been argued that SOCE inhibition during mitosis in Cos-7 cells is the result of the microtubule-network remodeling that accompanies mitosis (Russa et al, 2008).…”
Section: Soce Inactivates During Mitosismentioning
confidence: 99%
See 2 more Smart Citations
“…Similar indings were reported in COS-7 cells, where the treatment with nocodazole triggered the retraction of tubulin ilaments from cell periphery leading to the progressive loss of SOCE, similarly to what is found in mitosis. On the contrary, placlitaxel, which stabilizes microtubules, enhanced SOCE [36], supporting for a role of microtubules in the normal function of SOCE.…”
Section: Cytoskeletal Components Involved In the Control Of Socementioning
confidence: 74%